Reduction of employment protection in Europe: a comparative fuzzy-set analysis - Ochel, Wolfgang; Rohwer, Anja (Munich, 2009)
"Since the middle of the 1980s many European countries have reduced the strictness of their employment protection mainly by relaxing it for temporary jobs. These countries are Belgium, Denmark, Germany, Greece, Italy, the Netherlands, Portugal, Spain and Sweden. The article explores the conditions of the reduction of employment protection and takes a closer look at the combination of causal factors. It uses fuzzy-set qualitative comparative analysis (fuzzy-set QCA)."